KEBERADAAN DAN SERANGAN WALANG SANGIT (Leptocorisa spp.) SERTA BURUNG BONDOL (Lonchura spp.) PADA TANAMAN PADI - Mulyana, Ade Nendi; Russianzi, Wanda (Fakultas Pertanian Universitas Janabadra, 2026)
Pest infestation in rice plants is one of the factors that can disrupt rice production. This study aims to describe the presence and infestation conditions of Leptocorisa spp. (rice bug) and Lonchura spp. (munia birds) on rice plants from the milk ripening stage to grain maturation. Observations were conducted in a rice field in Bogor City, West Java, using a qualitative descriptive approach through direct observation, farmer interviews, and visual documentation. Field observations showed that Leptocorisa spp. attacks occurred during the milk ripening stage and were reported to be controllable through pesticide application, resulting in a relatively low impact on harvest yield. In contrast, Lonchura spp. attacks were observed starting from the early generative stage and increased during grain maturation. These attacks were difficult to control and often led to crop failure. The use of nets as a mechanical control method for Lonchura spp. has been implemented; however, its effectiveness depends on proper installation techniques. Visual documentation further revealed distinct characteristics of damage caused by the two pests on rice plants.